Translation Equivalence of Locative Prepositional Phrases in the Political Biography of Suharto by RE Elson - Pebri Prandika Putra (Universitas Islam Nahdlatul Ulama Jepara, 2022)
This research aims to find out to find out the types of translation equivalence of Locative Prepositional Phrases and to know the most dominant types of translation equivalence of Locative Prepositional Phrases found in Biography Suharto : A Political Biography by. R.E Elson. The method used in this research is qualitative research with content analysis approach. The analysis shows that there are two types of translation equivalence in the in Biography Suharto : A Political Biography by. R.E Elson. The types of translation equivalence of Locative Prepositional Phrases found are both formal equivalence and dynamic equivalence as 130 data. The formal equivalence shows total data 45 data or 34,6 %. The dynamic equivalence show total data 85 data or 65,4 %. The source language-oriented formal equivalence is maintained by the translator in the target language. while dynamic equivalence is oriented towards the target language where the translator prioritizes a good structure in the target language.The data shows that the most dominant type of translation equivalence in Biography Suharto by. R.E Elson : A Political Biography is Dynamic Equivalence. It is indicated by a situation when the source language is translated more accurately using dynamic equivalent techniques so that readability and acceptability in the target language is much better.